AB0154 Pathogenic Role of Irhom2 in Seropositive Rheumatoid Arthritis. (10th June 2014) - Kim, Y.J.; Lee, E.-J.; Hong, S.; Koo, B.S.; Seo, W.J.; Oh, J.; Kim, Y.-G.; Lee, C.-K.; Yoo, B.
Abstract : Background: Tumor necrosis factor (TNF)-α is a major pathologic cytokine in rheumatoid arthritis (RA) and the current target of RA treatment has been on blocking the TNF-α. iRHOM2 is a regulator of TNF-α convertase that mediate the release of TNF-α from immune cells. Moreover, immune complexes (ICs) are known to induce expression of iRHOM2 via Fc receptors (FcλRIIIa/CD16) in monocytes, regulating the production of TNF-α. Objectives: We hypothesized that the expression of iRHOM2 and Fc receptors are up regulated in seropositive RA patients, that is mediated by immune complex. Methods: The level of TNF-α was measured in the serum of seropositive (+) and seronegative (−) RA patients by ELISA. Messenger RNA expression of iRHOM2 and CD16 was evaluated on peripheral blood mononuclear cells of (+) RA, (−) RA patients, and healthy controls. ICs were extracted from serum of RA patients by adding polyethylene glycol. Isolated ICs were added to THP1-cell cultures to examine the induction of iRHOM2 and CD16. Results: Serum level of TNF-α was similar between (+) RA patients and (−) RA patients (3.23±(5.97) pg/ml vs. 1.99±(1.93) pg/ml). Increased iRHOM2 and CD16 mRNA expression was found on PBMC in (+) RA patients compared to those in (−) RA patients (figure). IC isolated from (+) RA patient could enhance the expression of iRHOM2 as well as CD16 from THP-1 cells. Conclusions: iRHOM2, highly expressed in (+) RA monocytes, might be regulated by immune complex containing anti-cyclic citrullinated peptides antibody, although serum TNF-α level was not different in (+) and (−) RA patient. References: Lichtenthaler SF. iRHOM2 takes control of rheumatoid arthritis. J Clin Invest 2013;123:560-2. Issuree PD, Maretzky T, McIlwain DR et al. iRHOM2 is a critical pathogenic mediator of inflammatory arthritis. J Clin Invest 2013;123:928-32. Cooper DL, Martin SG, Robinson JI et al. FcgammaRIIIa expression on monocytes in rheumatoid arthritis: role in immune-complex stimulated TNF production and non-response to methotrexate therapy. PLoS One 2012;7:e28918. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3199